DnaK Functions as a Moonlighting Protein on the Surface of Mycoplasma hyorhinis Cells - Li, Yao; Wang, Jia; Liu, Beibei; Yu, Yanfei; Yuan, Ting; Wei, Yanna; Gan, Yuan; Shao, Jia; Shao, Guoqing; Feng, Zhixin; Tu, Zhigang; Xiong, Qiyan (Frontiers in Microbiology, 2022)
Mycoplasma hyorhinis is a common pathogen of swine and is also associated with various human tumors. It causes systemic inflammation, typically polyserositis and polyarthritis, in some infected pigs. However, the pathogenic mechanism of M. hyorhinis remains unclear. DnaK is a highly conserved protein belonging to the heat-shock protein 70 family of molecular chaperones, which plays important roles as a moonlighting protein in various bacteria. In the present study, we identified the surface exposure of M. hyorhinis DnaK. The virulent strain expressed more DnaK on its surface than the avirulent strain. Thereafter, the potential moonlighting functions of DnaK were investigated. Recombinant M. hyorhinis DnaK (rMhr-DnaK) was found to be able to adhere to swine PK-15 cells and human NCI-H292 cells. It also bound to four extracellular matrix components—fibronectin, laminin, type Ⅳ collagen, and vitronectin—in a dose-dependent manner. ELISA demonstrated an interaction between rMhr-DnaK and plasminogen, which was significantly inhibited by a lysine analogue, ε-aminocaproic acid. rMhr-DnaK-bound plasminogen was activated by tissue-type plasminogen activator (tPA), and the addition of rMhr-DnaK significantly enhanced the activation. Finally, a DnaK-specific antibody was detected in the serum of pigs immunized with inactivated vaccines, which indicated good immunogenicity of it. In summary, our findings imply that DnaK is an important multifunctional moonlighting protein in M. hyorhinis and likely participates extensively in the infection and pathogenesis processes of M. hyorhinis.